Implementation of a program to strengthen oral hygiene in patient with cleft deformities: a prospective randomized controlled clinical trial - Camille Boeffard; Justine Loin; Roselyne Clouet; Alexis Gaudin; Pierre Corre; Tony Prud’Homme (Trials)
Abstract Background Cleft lip and/or palate is the most common congenital orofacial deformity, affecting 1/800 births. A thorough review of the literature has shown that children with cleft have poorer oral hygiene and dental health than other children, with higher levels of caries in both temporary and permanent teeth and poorer periodontal health. Cleft patients are treated by a multidisciplinary team that aims to provide comprehensive care from pre- or post-natal diagnosis to early adulthood and the end of growth. We aim to assess, through a single-center, prospective, randomized and controlled clinical trial conducted at the Nantes Cleft Centre, the impact of an enhanced dental program on oral hygiene and dental health in cleft patients. Methods Patients aged 3 to 15 years with unilateral or bilateral cleft lip and/or palate will be offered to participate in this study. After acceptance, patients will be randomly assigned to 2 groups: test group or control group. For the control group, there will be no change in the patient’s care, and they will continue to see their surgeon on an annual basis. For the test group, a 30–45-min consultation will be added to the annual check-up. During this visit, patients and their parents will receive oral and written oral hygiene instructions to improve oral hygiene knowledge and brushing technique. If necessary, dental treatment will be provided at the same appointment or at a later date. In addition, patients will be contacted via telemedicine every 2 months to increase motivation, and an additional dental appointment will be scheduled at 6 months. Discussion This is a single-center study which, if conclusive, could lead to a paradigm shift in the dental care pathway for cleft patients. Trial registration NCT05867862 submitted 2023–07-05 https://clinicaltrials.gov/study/NCT05867862?locStr=Nantes,%20France&country=France&state=Pays%20de%20la%20Loire&city=Nantes&distance=50&cond=CLEFT%20LIP&rank=1- -Trial Sponsor Nantes University Hospital. Trial status: 8th Version date 2023 May 05; recruitment began in June 2023 and will be completed in June 2024.